The effects of internal stresses on the creep deformation investigated using in-situ synchrotron diffraction and crystal plasticity modelling. (15th October 2021) - Mamun, Abdullah Al; Agius, Dylan; Simpson, Chris A.; Reinhard, Christina; Truman, Christopher; Mostafavi, Mahmoud; Knowles, David
Graphical abstract: Abstract: In this study we investigated the evolution of meso-scale internal stresses and those effects on local deformation behaviour during incremental plastic and creep deformation in type 316H stainless steel at 550 °C, using in-situ X-ray synchrotron diffraction and crystal plasticity modelling. Owing to the fast data accusation rate of synchrotron diffraction technique, for the first time, the transient behaviour of different grain families was captured during initial fast stress relaxation period of the displacement-controlled creep dwells. Significantly it is found that the evolution of internal stresses during time independent plastic deformation is distinct from that during time dependent creep deformation. During plastic deformation, lattice strains in the 3 1 1 grain family exhibit linear behaviour whereas during creep deformation it exhibits non-linear behaviour, instead the 1 1 1 grain family exhibit linear behaviour. A novel unified constitutive law was devised within crystal plasticity framework based on the theoretical physics; the model successfully predicts the macroscopic deformation behaviour as well as the distinction between the evolution of meso-scale internal stresses during plastic and creep deformation, therefore, correctly accounting for the effect of internal stresses generated during plastic deformation on the subsequent creep deformation. The validated model has elucidated the grain-neighbouring effects on individual grain deformations.